非关行役苦，显隐塞垣间 ：纳兰性德康熙二十一年边塞诗词之比较 = The feelings too intertwined to endure : a comparative study of Nalan Xingde's frontier-style poems and Ci poetry in twenty-first year of Kangxi (1682) - 胡欣然 Hu, Xinran (2013)
纳兰性德是清初杰出的诗人,词人，虽然身为满清贵胄，但他却厌恶高在庙堂的 朝廷生活，向往自由清简的普通生活。长期以来，学术界对纳兰词的关注度非常高，相比之下对其诗歌的研究稍微疏忽。本论文通过比较研究边塞诗词的代表阶段，即康熙二十一年，来挖掘纳兰性德在塞垣上亦显亦隐的思想情绪轨迹，获得更多关于纳兰其人的了解和他在清代前期边塞诗坛上独特的贡献和地位。第一章绪论之后，从第二、三章开始，将康熙二十一年纳兰性德的出塞经历分为两个阶段，分别比较两个时间段期间所作的边塞诗与边塞词，并解释缘何诗与词在感情表达上相差甚远，后推测导致这些异处的原因：少年理想不得志、爱妻早亡、父亲在朝中面对危机四伏、固疾缠身以及对侍卫生活的厌倦使他的思想比同时期的诗人更加复杂、这些复杂和矛盾常常体现在他的边塞诗词里。第四章单独分析纳兰性德边塞诗词的艺术手法之异，在于得出最后的结论：纳兰遵从“以自然之眼观物，以自然之舌言情”，纯任性灵的抒写风格。第五章，首先讨论康熙二十一年所作的边塞作品在他一生中所有边塞诗词中具有代表性，然后再以这样有代表性的诗词和清代前期其他边塞文人的边塞作品作比较，突出纳兰边塞诗词的特色和独特地位。Nalan Xingde was an outstanding poet in the early Qing Dynasty. Although being a Manchu noble, he did not enjoy leading a life in court as he had been longing for freedom outside the court. Over the years, there has been more attention given to Nalan Xingde’s Ci than his poems. This thesis is a comparative study of the frontier poems and Ci written during twentyfirstyear of Kangxi which were able to represent all other frontier poems and Ci written by Nalan Xingde. The ultimate purpose is to study the poet’s ideology and emotional changes, as well as understanding Nalan’s unique contributions and status in the Early Qing frontier-style literature works. Following the first chapter of this thesis, the second and third chapters will start bydividing; Nalan Xingde’s experience in the twenty- first year of Kangxi into two phases. Then compare the frontier poems with Ci which were written within these two periods, and explain why emotions reflected by poems were a far cry from the emotions reflected by Ci. This was largely due to the unfulfilled ambition, death of his beloved wife, his father’s dangerous situations in court, chronic disease and tiredness of being a guard to the Emperor. All these made his thought and personality more complicated than other poets of the early Qing Dynasty. The fourth chapter analyses the differences between artistic techniques used in Nalan Xingde’s frontier poems and Ci which aims to show that Nalan Xingde created his literature works based on his most genuine and natural feelings. The fifth chapter first showed the value of frontier poems and Ci made during the twenty-first year of Kangxi as compared to all other frontier poems written by him, followed by further discussions on the uniqueness and contributions of Nalan Xingde’s frontier poems and Ci in the Early Qing Dynasty.